Low dose subcutaneous adrenaline to prevent acute adverse reactions to antivenom serum in people bitten by snakes: randomised, placebo controlled trial - Anuja Premawardhena; C E de Silva; M.M.D. Fonseka; Saman B. Gunatilake; H J de Silva (1999)
To assess the efficacy and safety of low dose adrenaline injected subcutaneously to prevent acute adverse reactions to polyspecific antivenom serum in patients admitted to hospital after snake bite.Prospective, double blind, randomised, placebo controlled trial.District general hospital in Sri Lanka.105 patients with signs of envenomation after snake bite, randomised to receive either adrenaline (cases) or placebo (controls) immediately before infusion of antivenom serum.Adrenaline 0.25 ml (1:1000).Development of acute adverse reactions to serum and side effects attributable to adrenaline.56 patients (cases) received adrenaline and 49 (controls) received placebo as pretreatment. Six (11%) adrenaline patients and 21 (43%) control patients developed acute adverse reactions to antivenom serum (P=0.0002). Significant reductions in acute adverse reactions to serum were also seen in the adrenaline patients for each category of mild, moderate, and severe reactions. There were no significant adverse effects attributable to adrenaline.Use of 0.25 ml of 1:1000 adrenaline given subcutaneously immediately before administration of antivenom serum to patients with envenomation after snake bite reduces the incidence of acute adverse reactions to serum.